Exploring households’ recycling behaviour in a World Heritage City, Melaka - Goh, Mei Ling; Yoon, David Kin Tong; Elsadig Musa Ahmed (Penerbit Universiti Kebangsaan Malaysia, 2018)
The aim of this study is to examine the determinants of household recycling behaviour from the perspective of the Theory of Planned Behaviour (TPB). Attitudes towards recycling, subjective norms, perceived behavioural control, commitment to the environment and intention to recycle were hypothesised to explain recycling behaviour. Data was collected using stratified sampling via a questionnaire survey involving 444 households from Melaka. The model was validated and tested using structural equation modelling. The findings confirmed that all the hypotheses developed were supported, with an R2 value of 66.7%. This study contributes to the field by introducing a new perspective on research into recycling behaviour, incorporating an additional variable, commitment to the environment, in the TPB model. It provides new empirical findings for government policy makers and other agencies to help develop policies and regulations in relation to the sustainability of household recycling behaviour. It is recommended that other variables be included and a longitudinal research design adopted to overcome the limitations of this study in future research.